Implementasi Model Pembelajaran Team Game Tournament untuk Meningkatkan Hasil Belajar Bahasa Inggris - Mohammad Umar (Balai Diklat Keagamaan Semarang, 2021)
The problem of this research is whether the Team Game Tournament Learning Model (TGT) can improve the English learning achievement of calss XI IPS-3 students of MAN 1 Kudus in the even semester of the academic year 2018/2019. The purpose of this study is to find out that the implementation of the Team Game Tournament Learning Model (TGT) can improve English learning achievement of class XI IPS-3 students of MAN 1 Kudus in the even semester of the academic year 2018/2019. The results of the study showed that there is an improvement of the English learning achievement of class XI IPS-3 students. The improvement was indicated by: (1) the average learning achievement in cycle I is 7.14; cycle II 7.44; and 8.84 in cycle III; (2) the learning completion in cycle I is 47.22% of all students and the incompleted students is 52.78%; the completed students in cycle II is 72.22% and the incompleted students is 27.78%; in cycle III, the completed students in cycle III is 100%; (3) the classical learning completion in cycle I is 47.22%, in cycle II reaches 72.22; cycle III reaches 100%.